Fórum permanente de conselhos escolares no município de Vitória/ES: uma proposta para o diálogo, democracia e formação cidadã - Motta, Fatima Dias da (2022)
The research has reference to the constitutive process of the School Councils and its history at the Municipal Education in Vitória/ES, its composition, operation and organization, having as object of study the movements in the implementation of Permanent School Councils Forum. The research is based on a perspective the democratization contexts of instituting democratic organization with a focus on school councils and their possibilities to overcome the locality with a view to proposals for regional political organization and its presence in the context of democratic school management, understanding democratic management as the right to participate in discussions and deliberations that are concerned to public education. It aims at analyzing the different contexts and situations in which the School Council Forum was called and discussed along the formative and constitutive history of the School Council at the Municipal Education in Vitória. This is a qualitative, exploratory research in which elements of critical collaboration research and document research are used. As data collection techniques, questionnaires and semi-structured interviews are used. The work was developed with representatives from the school councils of the seven administrative regions, City Council Education members and technicians of the Municipal Secretariat of Education. It is concluded that the deepening of democratic management and citizen training in the sense of strengthening School Councils depend on several factors, among them, the involvement and commitment of the school community in the effort to develop a culture of active participation and the creation of public policies that make it possible. As final product, material for School Councilors is created, in booklet format, with theoretical concepts about School Council and democratic management; propositions for the implementation of a Permanent School Councils Forum and a draft for the institution of the referred forum.